Promoting Healthy Sexual Behaviours through Comprehensive Sexuality Education - Rosy Shah; Amrit Pokhrel (Journal of Nepal Medical Association, 2023)
Comprehensive sexuality education is a scientifically accurate global program that encompasses the variable aspects necessary for achieving healthy sexual and reproductive health in children of schoolgoing age. It provides a holistic approach to developing sound knowledge and a positive attitude in a manner that does not blatantly refute the established sociocultural norms but rather delicately treads around them to bust unhealthy practices through age-appropriate measures. It is deemed necessary for health professionals to be appropriately trained to better convey sensitive information regarding sexual and reproductive well-being in a manner that is acceptable and effective, especially in the context of orthodox communities.